SIMULASI TINGKAT KEBISINGAN DAN KADAR POLUTAN SEBAGAI AKIBAT AKTIVITAS TRANSPORTASI PADA KAWASAN PERDAGANGAN DI KOTA KENDARI (Studi kasus: Kawasan Perdagangan Jalan MT. Haryono Kec. Wua-wua Kota Kendari) - Djalante, Susanti; Nurrakhmad, Laode Muh; Sugiyarto, Try (MEKTEK, 2013)
The rapid economic activity in Kendari  is indicated by  development of  central business  Lippo Plaza in MT.Haryono Roads Kendari. However, the consequences of the development of the central business  LippoPlaza  have affected on the environment in the form of increased noise and air pollution. The aim  of thisstudy was to determine the level of noise and air pollution in the existing conditions, and to determine thelevel of noise simulation.  The method  used in this study for the noise calculations  was based on " The Bookof Calculation of Road Traffic Noise " published by the Department of Transport , Welsh Office , HMSO(1988), and the method of calculation of pollutant concentration  used  an equation developed by SitiMalkamah. The results of this study showed that the highest noise levels occur on Holidays / Saturday in Segment 2 (front Jl.MT.Haryono Lippo Plaza ) of 70.11 dB ( A ), this value is above the noise quality standardssuggested by No. KepMenLH . 48 in 1996 , which is 70 dB ( A ). In addition, the value also has  exceeded ofthe maximum allowed for trade in the region ( Zone C ) Regulation of the Minister of HealthNo.718/Men/Kes/XI/1987. Variables such as traffic volume is high and a large reflection angle, couldincrease noise, while low-speed, high barrier width and spacing can reduce the noise level.  For pollutantlevels, the value of 4065.33 μg/nm3 content of CO, NOx at 200-300 μg/nm3 , μg/nm3 PM at 0.0097 , stillbelow the National Ambient Air Quality Standards ( PP RI 41, 1999 ) , namely 30000 μg/nm3 , 400 and 150μg/nm3 μg/nm3. While the HC 400 and 700 μg/nm3 μg/nm3 has exceeded the standard of 160 μg/nm3 .Recommendation suggested to address the noise problem at Jl.MT . Haryono is the adoption of the CoreStrategy, which is the application of one direction on one arm of the intersection at peak hours , thusresulting intersection service level increases from E to C.Keywords: Noise Simulation, Pollutant Consentration Simulation